Improving the quality of life for premature infants through the continuity of care approach: A literature review - Dyah Dwi Astuti; Dessie Wanda (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background: The agenda for strengthening the global health architecture is to improve quality of life for premature infants. Premature births increase the morbidity and mortality of newborns, necessitating innovation in primary health care. Objectives: This study was conducted to examine innovation programs with a continuity of care approach in primary health care for premature infants in an effort to strengthen the global health architecture. Methods: A literature review method was used to analyze articles obtained using databases such as Science Direct and Google Scholar. The researcher used the key words “continuity of care” and “premature infants”. The inclusion criteria were full-text journal articles published from January 2020-December 2022 in English-language journals. Results: This study obtained ten articles that correspond to the continuity of care approach for premature infants. The articles included four qualitative studies, three quantitative studies, one mixed-method study, one literature review, and one systematic review. There are three themes related to the continuity of care for premature infants, including (1) Primary healthcare with information continuity, relationships continuity, and management continuity; (2) Continuity of care in the antenatal, natal, and postnatal periods; (3) The continuity of care on premature infant approach improves the outcome of premature infant care, the ability of parents, and health service quality. Conclusions: A continuity of care approach can increase the achievement of adequacy, equity, efficiency, and effectiveness in primary health care for premature infants. Joint synergy between the community, health services, and health policymakers is essential in efforts to strengthen the quality of life for premature infants.